1997
DOI: 10.1097/00001756-199709080-00006
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sciatic nerve transection induces TUNEL labeling of neurons in the rat spinal cord and DRG

Abstract: Transection of a peripheral nerve in neonatal rats induces an extensive death of axotomized neurons. We demonstrate here that spinal motoneurons and sensory dorsal root ganglia neurons become TUNEL-labeled after sciatic nerve transection in neonatal rats, thus indicating that apoptotic mechanisms are involved in the death process. Interestingly, there is also a profound increase of TUNEL-labeled interneurons in the deep dorsal horn. This location suggests that an intact afferent input and/or contact with targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
2
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 8 publications
0
27
2
1
Order By: Relevance
“…Several lines of evidence that indicate that both developing neurones and glial cells die by apoptosis following injury to a peripheral nerve or to the spinal cord (Lawson and Lowrie, 1998;Liu et al, 1997;Oliviera et al, 1997), although some necrotic cell death does take place (Li et al, 1998). In this study, we found that hsp27 immunoreactive motoneurones did not co-express markers of apoptosis.…”
Section: Discussioncontrasting
confidence: 41%
“…Several lines of evidence that indicate that both developing neurones and glial cells die by apoptosis following injury to a peripheral nerve or to the spinal cord (Lawson and Lowrie, 1998;Liu et al, 1997;Oliviera et al, 1997), although some necrotic cell death does take place (Li et al, 1998). In this study, we found that hsp27 immunoreactive motoneurones did not co-express markers of apoptosis.…”
Section: Discussioncontrasting
confidence: 41%
“…16 Another major risk factor is the immaturity of the individual; motoneuron cell death is much more prevalent following axotomy in newborn rodents. 41,42 Neonatal nerve injury-induced motoneuron loss is mediated by excitotoxic mechanisms and is apoptotic in nature. 27 The time course of apoptotic cell death following spinal nerve root avulsion evolves relatively rapidly, within several days, 27,32 and therefore can be partially reversed by prompt infusion of growth factors and neurotrophins.…”
Section: Cell Death Of Motoneuron After Nerve Injuriesmentioning
confidence: 99%
“…We have shown that apoptotic death may underlie the loss of spinal motoneurons, DRG neurons, and interneurons in the spinal cord after neonatal sciatic nerve transection (Oliveira et al, 1997). In this situation, the loss of interneurons coincides with the programmed apoptotic death of such neurons, which occurs from birth up to the sixth postnatal day in the rat (Lawson et al, 1997), whereas PCD of motoneurons and DRG neurons takes place prenatally (Harris and McCaig, 1984;Oppenheim, 1991;Coggeshall et al, 1994).…”
mentioning
confidence: 93%